An Ode to Salonika : The Ladino Verses of Bouena Sarfatty - Melammed, Renee Levine (Book collections on Project MUSE., 2013)
Through the poetry of Bouena Sarfatty (1916-1997), this book sketches the life and demise of the Sephardi Jewish community that once flourished in this Greek crossroads city. A resident of Salonika who survived the Holocaust as a partisan and later settled in Canada, Sarfatty preserved the traditions and memories of this diverse and thriving Sephardi community in some 500 Ladino poems known as coplas. The coplas also describe the traumas the community faced under German occupation before the Nazis deported its Jewish residents to Auschwitz.